2017
DOI: 10.1007/s00392-017-1090-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk for life-threatening arrhythmia in newly diagnosed peripartum cardiomyopathy with low ejection fraction: a German multi-centre analysis

Abstract: IntroductionPeripartum cardiomyopathy (PPCM) is a rare cardiomyopathy characterized by an acute reduction in left ventricular ejection fraction (LVEF). Sudden deaths during the course of PPCM are reported to be elevated, the underlying mechanisms remains unknown. The aim of the present multi-centre study was to evaluate the arrhythmia burden in a multi-centre approach in patients with PPCM using a wearable cardioverter/defibrillator (WCD).Methods and resultsForty-nine patients from 16 German centres with newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 18 publications
2
45
0
4
Order By: Relevance
“…Given these well-recognized hazards, it is vitally important that zero- or near-zero-fluoroscopic approaches in EP are explored and refined, to minimise risks. These are especially important in high-risk populations, including children, pregnant women, and women with child-bearing potential [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Given these well-recognized hazards, it is vitally important that zero- or near-zero-fluoroscopic approaches in EP are explored and refined, to minimise risks. These are especially important in high-risk populations, including children, pregnant women, and women with child-bearing potential [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…In the US between 2004 and 2011, 2.1% of women with PPCM had a cardiac arrest, and 2.9% underwent implantation of a cardiac device 12. In a German series of 49 women with PPCM and LVEF, ≤35% of whom used wearable cardioverter defibrillators for 120 days, six patients experienced ventricular tachyarrhythmias; these arrhythmias included five episodes of ventricular fibrillation, two episodes of sustained ventricular tachycardia, and one episode of non-sustained ventricular tachycardia 112. An analysis of 9841 hospital admissions for PPCM in the US found that arrhythmias occurred in 18.7% of cases, with ventricular tachycardia occurring in 4.2% 113…”
Section: Natural Course and Prognosismentioning
confidence: 99%
“…In a German retrospective analysis, a remarkably high number of six out of 49 PPCM patients (12%) suffered from life-threatening arrhythmia [37]. Most of the PPCM patients fully recover or at least improve significantly within 3–6 months and the risk of malignant arrhythmia thereby decreases.…”
Section: Therapymentioning
confidence: 99%
“…Hence, immediate implantation of a permanent cardioverter/defibrillator (ICD) does not appear to be appropriate. Instead, the use of a wearable cardioverter/defibrillator (WCD; LifeVest®, Zoll, Pittsburgh, PA, USA) is recommended to prevent SCD [7, 29, 37]. In patients who do not recover LV function (LVEF ≤35%) despite optimal medical therapy or those who experience ventricular tachycardia with hemodynamic instability or ventricular fibrillation, implantation of an ICD (either transvenous or subcutaneous) or a cardiac resynchronization device defibrillator (CRT-D) is recommended according to current guidelines [29].…”
Section: Therapymentioning
confidence: 99%